Micro-shear bond strength and surface micromorphology of a feldspathic ceramic treated with different cleaning methods after hydrofluoric acid etching - Henrique Caballero STEINHAUSER; Cecília Pedroso TURSSI; Fabiana Mantovani Gomes FRANÇA; Flávia Lucisano Botelho do AMARAL; Roberta Tarkany BASTING (University of São Paulo, 2014)
Objective: The aim of this study was to evaluate the effect of feldspathic ceramic surface cleaning on micro-shear bond strength and ceramic surface morphology. Material and Methods: Forty discs of feldspathic ceramic were prepared and etched with 10% hydrofluoric acid for 2 minutes. The discs were randomly distributed into five groups (n=8): C: no treatment, S: water spray + air drying for 1 minute, US: immersion in ultrasonic bath for 5 minutes, F: etching with 37% phosphoric acid for 1 minute, followed by 1-minute rinse, F+US: etching with 37% phosphoric acid for 1 minute, 1-minute rinse and ultrasonic bath for 5 minutes. Composite cylinders were bonded to the discs following application of silane and hydrophobic adhesive for micro-shear bond strength testing in a universal testing machine at 0.5 mm/min crosshead speed until failure. Stereomicroscopy was used to classify failure type. Surface micromorphology of each treatment type was evaluated by scanning electron microscopy at 500 and 2,500 times magnification. Results: One-way ANOVA test showed no significant difference between treatments (p=0.3197) and the most common failure types were cohesive resin cohesion followed by adhesive failure. Micro-shear bond strength of the feldspathic ceramic substrate to the adhesive system was not influenced by the different surface cleaning techniques. Absence of or less residue was observed after etching with hydrofluoric acid for the groups US and F+US. Conclusions: Combining ceramic cleaning techniques with hydrofluoric acid etching did not affect ceramic bond strength, whereas, when cleaning was associated with ultrasound, less residue was observed.